Hubungan Kekerabatan Tanaman Talas (Colocasia esculenta (L.) Schott) di Kabupaten Bengkayang Berdasarkan Karakter Morfologi - Ara, Chilliany; Wardoyo, Elvi Rusmiyanto Pancaning; Ifadatin, Siti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Taro (Colocasia esculenta (L.) Scott) is a plant classified as a tuber derived from the genus Colocasia and belongs to the Araceae tribe. Analysis of kinship relationships can be done by observing morphological characters. The purpose of this study was to determine the relationship between taro plants in Bengkayang Regency based on morphological characters. This research was conducted from April to June 2023. Taking 30 samples in 6 sub-districts using purposive sampling method. Analysis of kinship relationships using the NTSys program with the UPGMA method. The results showed that 30 taro accessions had a similarity coefficient value of 0.52-0.93 or 52-93%. The results of kinship relationship analysis obtained 4 clusters at a similarity coefficient value of 0.60 or 60%. The results of morphological characterization based on qualitative and quantitative characters show that taro accessions have diversity in leaf and cormus characters of taro, especially in color characters.